THE INFLUENCE OF CONSUMER BUYING MOTIVES ON PURCHASING SUBSIDIZED HOUSES OF REAL ESTATE DEVELOPER - Pondaag, Cloudian E.; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2019)
Abstract: Subsidized houses is a program of Indonesian government that is designated specifically for low-income people. In making a purchase decision there will certainly be many factors such as, someone's motives in buying something for this case is buying a house. Buying motives are divided into two main classifications: the rational motive and emotional motive. This study aims to find out the influence of rational buying motives and emotional buying motives on consumer purchase decisions that buying a subsidized house provided by real estate developer PT Bangun Minanga Lestari. This type of research use multiple linear regression test with 65 respondents who have bought and owned a subsidized house of PT Bangun Minanga Lestari. Findings of the research show that all the attributes of consumer buying influence influence the purchase decision of subsidized houses simultaneously. Meanwhile partially, rational buying motives have an influence on purchasing subsidized houses and emotional buying motives does not have an influence on purchasing subsidized houses. Customers feels that the price, ease, their benefits and reliability are the important things in order to buying a new house. Government should more concern about the customer’s rational buyig motivesin order to encourage customer purchae decision.Keywords: consumer buying motives, rational buying motives, emotional buying motives, subsidized houses